Enactus UMP mobility programme in India - UMP, PNC (Pejabat Naib Canselor, 2016)
Universiti Malaysia Pahang (UMP) staff and members of Enactus UMP Club went to India in April this year to carry out various community services under the Enactus mobility programme called ‘Boosting Opportunity Beyond Border’.